Cholesterol and Linoleic Acid: a forgotten cooperation? Cholesterol: is still a negative myth? - Cocchi, Massimo; Minuto, Chiara (Progress in Nutrition, 2020)
This mini review proposes a reflection on the role of cholesterol in its cooperation with oxygen and linoleic acid. The authors deal with the logics of membrane mobility, where the concentrations of cholesterol and linoleic acid exert a strong influence on the dynamics of the greater or lesser entry of oxygen and, therefore, on the impact in the determinism of oxidative phenomena.